THE CORRELATION BETWEEN STUDENTS’ LEARNING STYLE AND THEIR SPEAKING ACHIEVEMENT IN ENGLISH EDUCATION STUDY PROGRAM - Malessy, Gidalthy; Lekawael, Rosina; Patty, Jusak (Pattimura Excellence Journal of Language and Culture, 2025)
The research context in this study is to find a correlation between students' learning styles and their achievement in speaking courses. This study aims to determine whether or not there is a correlation between students' learning styles (as variable X) and their achievement in speaking class (as variable Y) in odd-semester students in 2023 at Pattimura University. There were 54 students taken as the sample of this study who were determined by using simple random sampling. The collected data were analyzed by using Pearson Product Moment Correlation and the instruments used were students’ speaking achievement and questionnaire. The results showed that the visual learning style had the highest mean value among the three types. Based on rxy: 0.624, the correlation between students’ learning styles and their speaking achievement is strong. Speaking fluency is a key indicator of language learning, and understanding one's learning style can help students learn more efficiently and successfully.